Provoking feminisms - Allen, Carolyn; Howard, Judith A. (The University of Chicago Press, 2000)
Un livre stimulant et incisif, Provoking Feminisms est une collection d'essais, de commentaires et de réponses sur certaines des questions les plus controversées de la théorie féministe d'aujourd'hui. Des conversations spécifiques sont centrées sur des sujets de débat tels que la théorie du point de vue féministe ; le genre comme catégorie analytique ; problèmes de "différence" sexuelle ; et la vie privée et les représentations du personnel. Chaque échange parle puissamment des enjeux actuels au cœur de l'érudition féministe et comprend des discussions à partir d'un échantillon de disciplines : théorie politique/sociale, philosophie, sociologie, études culturelles et théorie critique. Intense et rigoureux, Provoking Feminisms est un ouvrage crucial pour quiconque s'intéresse à l'état de l'érudition féministe contemporaine.
Keywords: anthologie; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; point de vue situé; sciences humaines; thématiques; épistémologie

Heterosexuals' use of "fag" and "queer" to deride one another: a contributor to heterosexism and stigma - Burn, S M (Journal of homosexuality, 2000)
This paper is on heterosexuals' use of words such as "fag" and "queer" to refer to one another in an insulting manner. This behavior perpetuates heterosexism and the stigmatization of gays. Two hundred and fifty-seven university students (73% Euro-American) served as participants. Males exhibited more anti-gay prejudice and anti-gay behavior than females. Heterosexual males frequently used words such as "fag" and "queer" to put one another down. Anti-homosexual prejudice was predictive of anti-gay behavior. However, approximately half of those who engaged in the behavior were not strongly anti-homosexual. For these individuals, the behavior may win approval from their social group. Awareness campaigns and peer reminders that the derisive use of "fag" and "queer" harms homosexuals may be effective in changing this group. It is more difficult to reduce this behavior in individuals with strong anti-homosexual attitudes. The role of individuals and educational and work organizations in bringing about change is discussed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétérosexisme; insultes; premier cycle; psychologie; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Coming Out of the Castle: Gothic, Sexuality and the Limits of Language - Grove, Allen W. (Historical Reflections / Réflexions Historiques, 2000)
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; histoire; histoire et politique; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; thématiques; études littéraires

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Columbia University Press, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Section: xxii, 156 p. ; 24 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme